Securing Stability and Growth in a Shock Prone Region: The Policy Challenge for Latin America - Ricardo Hausmann; Michael Gavin (Inter-American Development Bank, Office of the Chief Economist, 1996)
What are the reasons for and the costs of Latin America`s volatility? Because there is no consensus on these fundamental questions, there is no consensus on the appropriate policy response to macroeconomic volatility in Latin America, and other shock-prone countries. This paper provides new evidence on these contentious issues, and discusses policy implications for the region.
Keywords: 330